A low surface energy super hydrophobic drag reduction anti-corrosion coating and preparation method thereof
Through the three-layer structure of low-surface energy superhydrophobic resistance-reducing and anti-corrosion coating, combined with epoxy resin, micron-scale polytetrafluoroethylene and fluorinated nanosilicon dioxide particles, the corrosion and resistance problems of ships during offshore operation are solved, and the corrosion and resistance problems of ships are achieved. It has efficient drag reduction and corrosion protection effects, and improves speed and energy utilization efficiency.
Patent Information
- Application Number
- CN202410483636.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-04-22
AI Technical Summary
Ships face corrosion, frictional drag and non-essential energy waste when operating at sea, and need a functional coating that combines corrosion and drag reduction to increase speed, reduce energy consumption and maintenance costs.
Using a three-layer structure, low-surface energy superhydrophobic resistance-reducing and anti-corrosion coating, the bottom layer uses epoxy resin, the middle layer introduces chemically inert low-surface energy micron particles, and the top layer forms a solid through the interaction between glass fiber powder and resin. Stable network micro-nanostructures and the introduction of fluorinated nanosilicon dioxide particles in an alkaline environment reduces surface energy and imparts superhydrophobic properties.
The coating is achieved with a strong stability, good anti-corrosion and anti-fouling performance, while maintaining super-hydrophobic properties, significantly improving the ship's speed and energy utilization efficiency, and reducing fuel consumption and maintenance costs.
Smart Images

Figure CN118460060B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anti-corrosion coating preparation, and specifically relates to a low surface energy super hydrophobic drag reduction anti-corrosion coating and a preparation method thereof. Background Art
[0002] As the main marine vehicle, the development of the marine transportation industry and the construction of maritime national defense are inseparable from it, and the importance of ship operation in the construction of the marine industry is becoming more and more significant. With the continuous prosperity of the marine industry, the demand for energy and hull maintenance required by ships during navigation has increased sharply. The long-term operation of ships is not only corroded by seawater for a long time, but also affected by friction resistance, which affects the operation state of the ship; at the same time, the turbulent boundary layer formed by the hull surface and the flow of seawater will also affect the hull speed; if it is operated at sea for a long time, a large number of marine organisms will attach to the bottom of the hull, increasing the weight of the hull and causing uncontrollable waste of fuel resources. Therefore, preventing corrosion on the hull surface, reducing the resistance of the ship during operation, and reducing unnecessary energy waste can effectively improve energy utilization efficiency. Therefore, the development of a functional coating with both anti-corrosion and drag reduction is of great significance to increase the speed of ships, reduce energy consumption, save fuel and maintenance costs, and achieve green navigation. Summary of the invention
[0003] The problem to be solved by the present invention is to develop a functional coating with both anti-corrosion and drag reduction properties. The present invention proposes a low surface energy super hydrophobic drag reduction anti-corrosion coating and a preparation method thereof.
[0004] To achieve the above object, the present invention is implemented through the following technical solutions:
[0005] A method for preparing a low surface energy super-hydrophobic drag-reducing anti-corrosion coating comprises the following steps:
[0006] S1. Prepare a primer, the primer is made of an epoxy resin solution, a fluorinated silane coupling agent, a leveling agent, and a defoaming agent, wherein the weight portions are 60-100 parts of an epoxy resin solution, 15-25 parts of a fluorinated silane coupling agent, 1.3-2.6 parts of a leveling agent, and 1.2-2.4 parts of a defoaming agent, and the leveling agent and the defoaming agent are added to the epoxy resin solution;
[0007] S2. Preparing an intermediate layer coating, wherein the intermediate layer coating is made of epoxy resin, diluent, coupling agent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, wherein the weight portions are 50-75 parts of epoxy resin, 10-14 parts of diluent, 10-15 parts of coupling agent, 10-20 parts of micron-grade polytetrafluoroethylene powder, 2-4 parts of dispersant, 1-2 parts of leveling agent, and 1-2 parts of defoaming agent;
[0008] S3. Prepare a top coating, the top coating is made of perfluorodecyl triethoxysilane modified nano-silica, glass fiber powder, epoxy resin, fluorinated silane coupling agent, solvent, and the weight parts are 5-10 parts of perfluorodecyl triethoxysilane modified nano-silica, 5-10 parts of glass fiber powder, 10-20 parts of epoxy resin, 4-8 parts of fluorinated silane coupling agent, 50-70 parts of solvent, 1-2 parts of leveling agent, 1-2 parts of defoaming agent, 2-4 parts of dispersant;
[0009] S4. Pour the base coating obtained in step S1 into a spray gun and spray it onto the substrate until it completely covers the substrate, then pour the middle layer coating obtained in step S2 into a spray gun and spray it onto the substrate until it completely covers the base coating, the obtained coating is placed in a 40-50°C oven for curing for 15-20 minutes, taken out and then sprayed with the top layer coating obtained in step S3 until the coating is completely covered, then naturally dried or moved to a 40-80°C oven for curing for 3-4 hours to obtain the low surface energy super hydrophobic drag reduction and anti-corrosion coating.
[0010] Furthermore, the preparation method of step S1 comprises the following steps:
[0011] S1.1. Prepare an epoxy resin solution, mix 10-25 parts of epoxy resin and 50-75 parts of ethanol solution, stir magnetically at 30-50 ° C for 2-3h to obtain a uniformly dispersed epoxy resin solution, and then add a leveling agent and a defoaming agent to obtain a first mixed solution;
[0012] S1.2. Prepare a fluorinated silane coupling agent, add 4-10 parts of a silane coupling agent to 20-50 parts of an ethanol solution, add 5-10 parts of aqueous ammonia, stir magnetically at 60-70° C. for 1-1.5 hours, then add 0.5-1.8 parts of perfluorodecyltriethoxysilane and 3-5 parts of ethyl orthosilicate, stir magnetically at 60-70° C. for 1.5-2 hours to obtain a fluorinated silane coupling agent;
[0013] S1.3. Add the fluorinated silane coupling agent obtained in step S1.2 to the first mixed solution obtained in step S1.1 according to the weight proportions, stir magnetically for 10-15 minutes, and obtain a base coating for later use.
[0014] Furthermore, the preparation method of step S2 is to mix the weighed epoxy resin, diluent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, and then ball mill for 1-2 hours at a ball mill speed of 600-1000r / min, and then add a coupling agent, stir evenly to obtain an intermediate layer coating.
[0015] Furthermore, the preparation method of step S3 comprises the following steps:
[0016] S3.1. Prepare perfluorodecyl triethoxysilane modified nano-silica, dissolve 5-10 parts of nano-silica in 40-50 parts of ethanol solution, add 10-15 parts of ammonia water and mix, stir magnetically at 60-70°C for 0.5-1h to obtain a uniformly dispersed nano-silica suspension; then add 0.5-1 part of perfluorodecyl triethoxysilane to 60-100 parts of ethanol, add 3-5 parts of tetraethyl orthosilicate, mix well, add the prepared nano-silica suspension and stir magnetically at 60-70°C for 3-4h, then centrifuge at a centrifugal speed of 4000r / min for 20-30min, and finally dry at 70-100°C for 3-5h to obtain perfluorodecyl triethoxysilane modified nano-silica;
[0017] S3.2. Dissolve the weighed perfluorodecyltriethoxysilane-modified nano-silica, glass fiber powder, and epoxy resin in a solvent, then add a leveling agent, a defoaming agent, and a dispersant, stir magnetically for 2-3 hours, then add a fluorinated silane coupling agent, mix for 10-15 minutes, and obtain a top coating.
[0018] Furthermore, the epoxy resin is bisphenol A epoxy resin, and the model of the epoxy resin is E51.
[0019] Furthermore, the solvent is ethanol or ethyl acetate, the coupling agent is a silane coupling agent, and the model of the silane coupling agent is KH-792.
[0020] Furthermore, the leveling agent is one of a polyether siloxane leveling agent or a polyurethane leveling agent, and the model of the leveling agent is TEGO Glide100, TEGO Glide410, HIRESOL200, and RM-2020NPR.
[0021] Furthermore, the dispersant is one of the polysiloxane dispersants, and the model of the dispersant is BYK-P104S, BYK102, BYK190.
[0022] Furthermore, the defoaming agent is one of the silicone defoaming agents, and the model of the defoaming agent is TEGOAirex931, AFE-0120, and Defom 6800.
[0023] A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating. A low surface energy super hydrophobic drag reduction anti-corrosion coating is prepared, and the drag reduction rate of the low surface energy super hydrophobic drag reduction anti-corrosion coating reaches 32.9%.
[0024] Beneficial effects of the present invention:
[0025] The present invention discloses a method for preparing a low surface energy super hydrophobic drag reduction and anti-corrosion coating, wherein the three-layer structure gives the coating excellent comprehensive performance. The bottom layer uses epoxy resin as a matrix to ensure the excellent bonding force of the coating and avoid the influence of the addition of fillers on the adhesion performance of the coating. The middle layer introduces chemically inert low surface energy micron particles of polytetrafluoroethylene, which not only reduces the surface energy of the coating but also serves as the skeleton structure of the entire coating, so that the nanoparticles of the top layer can be firmly fixed on the micron-sized protrusions through the bonding effect of the resin, thereby ensuring the mechanical properties of the coating. The top layer forms a strong and stable network micro-nano structure through the interaction between glass fiber powder and resin, and introduces fluorinated nano-silica particles prepared in an alkaline environment, further reducing the surface energy of the coating and giving the coating super hydrophobic properties. The pre-curing treatment between the middle layer and the top layer further improves the mechanical stability of the micro-nano structure of the coating, and the tertiary structure has a clear role, while ensuring that the coating has strong and stable super hydrophobic properties, it also has good anti-corrosion and anti-fouling properties.
[0026] The super hydrophobic drag reduction and anti-corrosion coating prepared by the method for preparing a low surface energy super hydrophobic drag reduction and anti-corrosion coating of the present invention not only has an anti-corrosion function, but also can maintain the super hydrophobic property of the coating surface for a long time, and has strong adhesion and a wide range of applicable substrates. The mechanical stability of the coating can be guaranteed during the long-term service of the coating, and the contact angle is greater than 150°, and the micro-nano structure on the surface is firm and stable, thereby ensuring the drag reduction effect of the coating, and even if the coating experiences friction and wear, it can still maintain a good drag reduction and anti-corrosion effect, and can achieve a long-term drag reduction and anti-corrosion effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a contact angle photograph of a super-hydrophobic drag-reducing and anti-corrosion coating prepared by a method in a specific embodiment of the present invention;
[0028] Figure 2 This is a contact angle photograph of a super-hydrophobic drag-reducing and anti-corrosion coating prepared by the method of the second specific embodiment of the present invention;
[0029] Figure 3 This is a contact angle photograph of a super-hydrophobic drag-reducing and anti-corrosion coating prepared by the third method of the specific embodiment of the present invention;
[0030] Figure 4 This is a comparison chart of the drag reduction rates of the super-hydrophobic drag reduction and anti-corrosion coatings prepared in the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the specific embodiments described are only part of the embodiments of the present invention, rather than all of the specific embodiments. The components of the specific embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations, and the present invention can also have other embodiments.
[0032] Therefore, the following detailed description of the specific embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected specific embodiments of the present invention. Based on the specific embodiments of the present invention, all other specific embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0033] In order to further understand the content, features and effects of the present invention, the following specific implementation methods are given as examples, and the attached Figure 1 -Attached Figure 4 The detailed instructions are as follows:
[0034] Embodiment 1:
[0035] A method for preparing a low surface energy super-hydrophobic drag-reducing anti-corrosion coating comprises the following steps:
[0036] S1. Prepare a primer, the primer is made of an epoxy resin solution, a fluorinated silane coupling agent, a leveling agent, and a defoaming agent, the weight parts of which are 60 parts of an epoxy resin solution, 16 parts of a fluorinated silane coupling agent, 1.4 parts of a leveling agent, and 1.4 parts of a defoaming agent, the leveling agent and the defoaming agent are added to the epoxy resin solution;
[0037] Furthermore, the preparation method of step S1 comprises the following steps:
[0038] S1.1. Prepare an epoxy resin solution by mixing 10 parts of epoxy resin and 50 parts of ethanol solution, stirring magnetically at 30 ° C for 3h to obtain a uniformly dispersed epoxy resin solution, and then adding a leveling agent and a defoaming agent to obtain a first mixed solution;
[0039] S1.2. Prepare a fluorinated silane coupling agent, add 4 parts of a silane coupling agent to 24 parts of an ethanol solution, add 5 parts of aqueous ammonia, and stir magnetically at 65° C. for 1 hour, then add 1.2 parts of perfluorodecyltriethoxysilane and 3 parts of ethyl orthosilicate, and stir magnetically at 65° C. for 1.5 hours to obtain a fluorinated silane coupling agent;
[0040] S1.3. The fluorinated silane coupling agent obtained in step S1.2 was added to the first mixed solution obtained in step S1.1 in parts by weight, and magnetically stirred for 10 min to obtain a primer for standby use;
[0041] S2. Preparing an intermediate layer coating, the intermediate layer coating is made of epoxy resin, diluent, coupling agent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, wherein the weight parts are 50 parts of epoxy resin, 15 parts of diluent, 10 parts of coupling agent, 20 parts of micron-grade polytetrafluoroethylene powder, 3 parts of dispersant, 1.5 parts of leveling agent, and 1.5 parts of defoaming agent;
[0042] Furthermore, the preparation method of step S2 is to mix the weighed epoxy resin, diluent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, and then ball-mill for 2 hours at a ball mill speed of 600 r / min, and then add a coupling agent, stir evenly to obtain an intermediate layer coating;
[0043] S3. Prepare a top coating, the top coating is made of perfluorodecyl triethoxysilane modified nano-silica, glass fiber powder, epoxy resin, fluorinated silane coupling agent, solvent, and the weight parts are 5 parts of perfluorodecyl triethoxysilane modified nano-silica, 5 parts of glass fiber powder, 20 parts of epoxy resin, 5 parts of fluorinated silane coupling agent, 60 parts of solvent, 1 part of leveling agent, 1 part of defoaming agent, and 2 parts of dispersant;
[0044] Furthermore, the preparation method of step S3 comprises the following steps:
[0045] S3.1. Prepare perfluorodecyltriethoxysilane modified nano-silica, dissolve 5 parts of nano-silica in 40 parts of ethanol solution, add 10 parts of ammonia water and mix, and stir magnetically at 60°C for 1 hour to obtain a uniformly dispersed nano-silica suspension; then add 1 part of perfluorodecyltriethoxysilane to 60 parts of ethanol, and add 4 parts of tetraethyl orthosilicate, mix well, add the prepared nano-silica suspension and stir magnetically at 60°C for 4 hours, then centrifuge at a centrifugal speed of 4000r / min for 30 minutes, and finally dry at 80°C for 4 hours to obtain perfluorodecyltriethoxysilane modified nano-silica;
[0046] S3.2. The weighed perfluorodecyl triethoxysilane-modified nano-silica, glass fiber powder, and epoxy resin were dissolved in a solvent, and then a leveling agent, a defoaming agent, and a dispersant were added. The mixture was stirred magnetically for 2 hours, and then a fluorinated silane coupling agent was added. After mixing for 15 minutes, a top coating was obtained.
[0047] S4. Pour the base coating obtained in step S1 into a spray gun and spray it onto the substrate until it completely covers the substrate, then pour the middle layer coating obtained in step S2 into a spray gun and spray it onto the substrate until it completely covers the base coating, the obtained coating is placed in a 45°C oven for curing for 20 minutes, taken out and sprayed with the top layer coating obtained in step S3 until the coating is completely covered, and then naturally dried to obtain the low surface energy super hydrophobic drag reduction and anti-corrosion coating.
[0048] Furthermore, the epoxy resin is bisphenol A epoxy resin, and the model of the epoxy resin is E51.
[0049] Furthermore, the solvent is ethanol or ethyl acetate, the coupling agent is a silane coupling agent, and the model of the silane coupling agent is KH-792.
[0050] Furthermore, the leveling agent is a polyether siloxane leveling agent or a polyurethane leveling agent, and the model of the leveling agent is TEGO Glide100.
[0051] Furthermore, the dispersant is a polysiloxane dispersant, and the model of the dispersant is BYK-P104S.
[0052] Furthermore, the defoaming agent is a silicone defoaming agent, and the model of the defoaming agent is TEGOAirex931.
[0053] The low surface energy super hydrophobic drag reduction anti-corrosion coating prepared by the method for preparing the low surface energy super hydrophobic drag reduction anti-corrosion coating described in this embodiment is subjected to a contact angle test. Figure 1 As shown, the contact angle is 156°.
[0054] Embodiment 2:
[0055] A method for preparing a low surface energy super-hydrophobic drag-reducing anti-corrosion coating comprises the following steps:
[0056] S1. Prepare a primer, the primer is made of an epoxy resin solution, a fluorinated silane coupling agent, a leveling agent, and a defoaming agent, wherein the weight parts are 60 parts of an epoxy resin solution, 15 parts of a fluorinated silane coupling agent, 1.3 parts of a leveling agent, and 1.5 parts of a defoaming agent, and the leveling agent and the defoaming agent are added to the epoxy resin solution;
[0057] Furthermore, the preparation method of step S1 comprises the following steps:
[0058] S1.1. Prepare an epoxy resin solution by mixing 10 parts of epoxy resin and 50 parts of ethanol solution, stirring magnetically at 30 ° C for 3h to obtain a uniformly dispersed epoxy resin solution, and then adding a leveling agent and a defoaming agent to obtain a first mixed solution;
[0059] S1.2. Prepare a fluorinated silane coupling agent, add 4 parts of a silane coupling agent to 24 parts of an ethanol solution, add 5 parts of aqueous ammonia, and stir magnetically at 65° C. for 1 hour, then add 1.2 parts of perfluorodecyltriethoxysilane and 3 parts of ethyl orthosilicate, and stir magnetically at 65° C. for 1.5 hours to obtain a fluorinated silane coupling agent;
[0060] S1.3. The fluorinated silane coupling agent obtained in step S1.2 was added to the first mixed solution obtained in step S1.1 in parts by weight, and magnetically stirred for 15 min to obtain a primer for standby use;
[0061] S2. Preparing an intermediate layer coating, the intermediate layer coating is made of epoxy resin, diluent, coupling agent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, wherein the weight parts are 55 parts of epoxy resin, 15 parts of diluent, 10 parts of coupling agent, 15 parts of micron-grade polytetrafluoroethylene powder, 3 parts of dispersant, 1.5 parts of leveling agent, and 1.5 parts of defoaming agent;
[0062] Furthermore, the preparation method of step S2 is to mix the weighed epoxy resin, diluent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, and then ball-mill for 2 hours at a ball mill speed of 600 r / min, and then add a coupling agent, stir evenly to obtain an intermediate layer coating;
[0063] S3. Prepare a top coating, the top coating is made of perfluorodecyl triethoxysilane modified nano-silica, glass fiber powder, epoxy resin, fluorinated silane coupling agent, solvent, and the weight parts are 8 parts of perfluorodecyl triethoxysilane modified nano-silica, 7 parts of glass fiber powder, 15 parts of epoxy resin, 5 parts of fluorinated silane coupling agent, 60 parts of solvent, 1 part of leveling agent, 1 part of defoaming agent, and 2 parts of dispersant;
[0064] Furthermore, the preparation method of step S3 comprises the following steps:
[0065] S3.1. Prepare perfluorodecyltriethoxysilane modified nano-silica, dissolve 5 parts of nano-silica in 40 parts of ethanol solution, add 10 parts of ammonia water and mix, and stir magnetically at 70°C for 1 hour to obtain a uniformly dispersed nano-silica suspension; then add 1 part of perfluorodecyltriethoxysilane to 60 parts of ethanol, and add 4 parts of tetraethyl orthosilicate, mix well, add the prepared nano-silica suspension and stir magnetically at 70°C for 3 hours, then centrifuge at a centrifugal speed of 4000r / min for 30 minutes, and finally dry at 80°C for 4 hours to obtain perfluorodecyltriethoxysilane modified nano-silica;
[0066] S3.2. The weighed perfluorodecyl triethoxysilane-modified nano-silica, glass fiber powder, and epoxy resin were dissolved in a solvent, and then a leveling agent, a defoaming agent, and a dispersant were added. The mixture was stirred magnetically for 2 hours, and then a fluorinated silane coupling agent was added. After mixing for 15 minutes, a top coating was obtained.
[0067] S4. Pour the base coating obtained in step S1 into a spray gun and spray it onto the substrate until it completely covers the substrate, then pour the middle layer coating obtained in step S2 into a spray gun and spray it onto the substrate until it completely covers the base coating, the obtained coating is placed in a 45°C oven for curing for 15 minutes, taken out and sprayed with the top layer coating obtained in step S3 until the coating is completely covered, then moved to a 60°C oven for curing for 3 hours to obtain the low surface energy super hydrophobic drag reduction and anti-corrosion coating.
[0068] Furthermore, the epoxy resin is bisphenol A epoxy resin, and the model of the epoxy resin is E51.
[0069] Furthermore, the solvent is ethanol or ethyl acetate, the coupling agent is a silane coupling agent, and the model of the silane coupling agent is KH-792.
[0070] Furthermore, the leveling agent is a polyether siloxane leveling agent or a polyurethane leveling agent, and the model of the leveling agent is TEGO Glide410.
[0071] Furthermore, the dispersant is a polysiloxane dispersant, and the model of the dispersant is BYK102.
[0072] Furthermore, the defoaming agent is one of the silicone defoaming agents, and the model of the defoaming agent is AFE-0120.
[0073] The low surface energy super hydrophobic drag reduction anti-corrosion coating prepared by the method for preparing the low surface energy super hydrophobic drag reduction anti-corrosion coating described in this embodiment is subjected to a contact angle test. Figure 2 As shown, the contact angle is 160°.
[0074] Embodiment 3:
[0075] A method for preparing a low surface energy super-hydrophobic drag-reducing anti-corrosion coating comprises the following steps:
[0076] S1. Prepare a primer, the primer is made of an epoxy resin solution, a fluorinated silane coupling agent, a leveling agent, and a defoaming agent, wherein the weight parts are 60 parts of an epoxy resin solution, 15 parts of a fluorinated silane coupling agent, 1.2 parts of a leveling agent, and 1.6 parts of a defoaming agent, and the leveling agent and the defoaming agent are added to the epoxy resin solution;
[0077] Furthermore, the preparation method of step S1 comprises the following steps:
[0078] S1.1. Prepare an epoxy resin solution by mixing 10 parts of epoxy resin and 50 parts of ethanol solution, stirring magnetically at 30 ° C for 3h to obtain a uniformly dispersed epoxy resin solution, and then adding a leveling agent and a defoaming agent to obtain a first mixed solution;
[0079] S1.2. Prepare a fluorinated silane coupling agent, add 4 parts of a silane coupling agent to 24 parts of an ethanol solution, add 5 parts of aqueous ammonia, and stir magnetically at 60° C. for 1 hour, then add 1.2 parts of perfluorodecyltriethoxysilane and 3 parts of ethyl orthosilicate, and stir magnetically at 60° C. for 1.5 hours to obtain a fluorinated silane coupling agent;
[0080] S1.3. The fluorinated silane coupling agent obtained in step S1.2 was added to the first mixed solution obtained in step S1.1 in parts by weight, and magnetically stirred for 10 min to obtain a primer for standby use;
[0081] S2. Prepare an intermediate layer coating, wherein the intermediate layer coating is made of epoxy resin, diluent, coupling agent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, wherein the weight parts are 60 parts of epoxy resin, 15 parts of diluent, 10 parts of coupling agent, 10 parts of micron-grade polytetrafluoroethylene powder, 3 parts of dispersant, 1.5 parts of leveling agent, and 1.5 parts of defoaming agent;
[0082] Furthermore, the preparation method of step S2 is to mix the weighed epoxy resin, diluent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, and then ball-mill for 2 hours at a ball mill speed of 600 r / min, and then add a coupling agent, stir evenly to obtain an intermediate layer coating;
[0083] S3. Prepare a top coating, the top coating is made of perfluorodecyl triethoxysilane modified nano-silica, glass fiber powder, epoxy resin, fluorinated silane coupling agent, solvent, and the weight parts are 10 parts of perfluorodecyl triethoxysilane modified nano-silica, 10 parts of glass fiber powder, 10 parts of epoxy resin, 5 parts of fluorinated silane coupling agent, 60 parts of solvent, 1 part of leveling agent, 1 part of defoaming agent, and 2 parts of dispersant;
[0084] Furthermore, the preparation method of step S3 comprises the following steps:
[0085] S3.1. Prepare perfluorodecyltriethoxysilane modified nano-silica. Dissolve 5 parts of nano-silica in 40 parts of ethanol solution, add 10 parts of ammonia water and mix, and stir magnetically at 60°C for 1 hour to obtain a uniformly dispersed nano-silica suspension; then add 1 part of perfluorodecyltriethoxysilane to 60 parts of ethanol, and add 4 parts of tetraethyl orthosilicate. After mixing evenly, add the prepared nano-silica suspension and stir magnetically at 60°C for 4 hours, then centrifuge at a centrifugal speed of 4000r / min for 30 minutes, and finally dry at 80°C for 4 hours to obtain perfluorodecyltriethoxysilane modified nano-silica;
[0086] S3.2. Dissolve the weighed perfluorodecyl triethoxysilane-modified nano-silica, glass fiber powder, and epoxy resin in a solvent, add a leveling agent, a defoamer, and a dispersant, stir magnetically for 2-3 hours, then add a fluorinated silane coupling agent, mix for 10-15 minutes, and obtain a top coating;
[0087] S4. Pour the base coating obtained in step S1 into a spray gun and spray it onto the substrate until it completely covers the substrate, then pour the middle layer coating obtained in step S2 into a spray gun and spray it onto the substrate until it completely covers the base coating, the obtained coating is placed in a 40-50°C oven for curing for 15-20 minutes, taken out and then sprayed with the top layer coating obtained in step S3 until the coating is completely covered, then naturally dried or moved to a 40-80°C oven for curing for 3-4 hours to obtain the low surface energy super hydrophobic drag reduction and anti-corrosion coating.
[0088] Furthermore, the epoxy resin is bisphenol A epoxy resin, and the model of the epoxy resin is E51.
[0089] Furthermore, the solvent is ethanol or ethyl acetate, the coupling agent is a silane coupling agent, and the model of the silane coupling agent is KH-792.
[0090] Furthermore, the leveling agent is a polyether siloxane leveling agent or a polyurethane leveling agent, and the model of the leveling agent is HIRESOL200.
[0091] Furthermore, the dispersant is a polysiloxane dispersant, and the model of the dispersant is BYK190.
[0092] Furthermore, the defoaming agent is a silicone defoaming agent, and the model of the defoaming agent is Defom6800.
[0093] The low surface energy super hydrophobic drag reduction anti-corrosion coating prepared by the method for preparing the low surface energy super hydrophobic drag reduction anti-corrosion coating described in this embodiment is subjected to a contact angle test. Figure 3 As shown, the contact angle is 164°.
[0094] The coating was tested for drag reduction using the rotating disk method. Figure 4 The drag reduction rate diagram of the coating prepared in Examples 1, 2, and 3 shows that the coating prepared in the present invention has excellent drag reduction performance, with a maximum drag reduction rate of 32.9%. Table 1 shows the performance of the coating prepared in Examples 1, 2, and 3
[0095] Table 1 Performance of low surface energy super hydrophobic drag reduction and anti-corrosion coating
[0096] project Example 1 Example 2 Example 3 Hydrophobic Angle 156° 160° 164° Roll Angle 2.8° 2.4° 1.0° Drag reduction rate 28.2% 32.9% 30.3% Corrosion voltage(V) -0.31 -0.22 -0.29 Anticorrosion efficiency (%) 92.3 95.4 96.8
[0097] As can be seen from Table 1, the super-hydrophobic coating prepared by the present invention, due to the inherent hydrophobicity of the coating interface, compared to the traditional surface coating, the water film formed on the super-hydrophobic surface can prevent the corrosive medium from penetrating the film, inhibit the formation of corrosion units, and thus enhance the anti-corrosion ability. In addition, the non-uniform micro-nano structure of the super-hydrophobic surface can capture a large amount of air in the air, greatly reducing the contact area and contact time between the surface and the water droplets, and the water droplets slide out of the surface due to the self-cleaning effect; for the super-hydrophobic surface immersed in the corrosive medium, the gas captured in the microstructure effectively improves the anti-corrosion ability of the super-hydrophobic surface in the corrosive medium as an air film between the solution and the metal surface. In short, the enhancement of waterproof ability and the gas retained on the surface inhibit the corrosion of the metal substrate.
[0098] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0099] Although the present application has been described above with reference to specific embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, as long as there is no structural conflict, the various features in the specific embodiments disclosed in the present application may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a low surface energy super hydrophobic drag reduction and anti-corrosion coating, It is characterized in that The steps include: S1. Preparing a primer, the primer is made of an epoxy resin solution, a fluorinated silane coupling agent, a leveling agent, and a defoaming agent, wherein the weight portions are 60-100 parts of an epoxy resin solution, 15-25 parts of a fluorinated silane coupling agent, 1.3-2.6 parts of a leveling agent, and 1.2-2.4 parts of a defoaming agent, and the leveling agent and the defoaming agent are added to the epoxy resin solution; S2. Preparing an intermediate layer coating, wherein the intermediate layer coating is made of epoxy resin, diluent, coupling agent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, wherein the weight portions are 50-75 parts of epoxy resin, 10-15 parts of diluent, 10-14 parts of coupling agent, 10-20 parts of micron-grade polytetrafluoroethylene powder, 2-4 parts of dispersant, 1-2 parts of leveling agent, and 1-2 parts of defoaming agent; S3. Preparing a top coating, the top coating is made of perfluorodecyl triethoxysilane modified nano-silica, glass fiber powder, epoxy resin, fluorinated silane coupling agent, solvent, leveling agent, defoaming agent, and dispersant, wherein the weight parts are 5-10 parts of perfluorodecyl triethoxysilane modified nano-silica, 5-10 parts of glass fiber powder, 10-20 parts of epoxy resin, 4-8 parts of fluorinated silane coupling agent, 50-70 parts of solvent, 1-2 parts of leveling agent, 1-2 parts of defoaming agent, and 2-4 parts of dispersant; S3.
1. Prepare perfluorodecyltriethoxysilane modified nano-silica, dissolve 5-10 parts of nano-silica in 40-50 parts of ethanol solution, add 10-15 parts of ammonia water and mix, stir magnetically at 60-70°C for 0.5-1h to obtain a uniformly dispersed nano-silica suspension; Then, 0.5-1 part of perfluorodecyl triethoxysilane is added to 60-100 parts of ethanol, and 3-5 parts of tetraethyl orthosilicate are added, and after being evenly mixed, the prepared nano-silica suspension is added and magnetically stirred at 60-70° C. for 3-4 hours, and then centrifuged at a centrifugal speed of 4000 r / min for 20-30 minutes, and finally dried at 70-100° C. for 3-5 hours to obtain perfluorodecyl triethoxysilane-modified nano-silica; S3.
2. Dissolve the weighed perfluorodecyltriethoxysilane-modified nano-silica, glass fiber powder, and epoxy resin in a solvent, add a leveling agent, a defoaming agent, and a dispersant, stir magnetically for 2-3 hours, then add a fluorinated silane coupling agent, mix for 10-15 minutes, and obtain a top coating; S4. Pour the base coating obtained in step S1 into a spray gun and spray it onto the substrate until it completely covers the substrate, then pour the middle layer coating obtained in step S2 into a spray gun and spray it onto the substrate until it completely covers the base coating, the obtained coating is placed in a 40-50°C oven for curing for 15-20 minutes, taken out and sprayed with the top layer coating obtained in step S3 until the coating is completely covered, then naturally dried or moved to a 40-80°C oven for curing for 3-4 hours to obtain the low surface energy super hydrophobic drag reduction and anti-corrosion coating.
2. A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to claim 1, It is characterized in that The preparation method of step S1 comprises the following steps: S1.
1. Prepare an epoxy resin solution, mix 10-25 parts of epoxy resin and 50-75 parts of ethanol solution, stir magnetically at 30-50°C for 2-3h to obtain a uniformly dispersed epoxy resin solution, and then add a leveling agent and a defoaming agent to obtain a first mixed solution; S1.
2. Prepare a fluorinated silane coupling agent, add 4-10 parts of a silane coupling agent to 20-50 parts of an ethanol solution, add 5-10 parts of aqueous ammonia, stir magnetically at 60-70° C. for 1-1.5 hours, then add 0.5-1.8 parts of perfluorodecyltriethoxysilane and 3-5 parts of ethyl orthosilicate, stir magnetically at 60-70° C. for 1.5-2 hours to obtain a fluorinated silane coupling agent; S1.
3. Add the fluorinated silane coupling agent obtained in step S1.2 to the first mixed solution obtained in step S1.1 according to weight proportions, and stir magnetically for 10-15 minutes to obtain a base coating for later use.
3. A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to claim 1 or 2, It is characterized in that The preparation method of step S2 is to mix the weighed epoxy resin, diluent, micron-grade polytetrafluoroethylene powder, dispersant, leveling agent, and defoaming agent, and then ball mill for 1-2 hours at a ball mill speed of 600-1000r / min, and then add a coupling agent, stir evenly to obtain an intermediate layer coating.
4. A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to claim 3, It is characterized in that The epoxy resin is bisphenol A type epoxy resin.
5. A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to claim 4, It is characterized in that The solvent is ethanol or ethyl acetate, and the coupling agent is a silane coupling agent.
6. A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to claim 5, It is characterized in that The leveling agent is a polyether siloxane leveling agent or a polyurethane leveling agent.
7. A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to claim 6, It is characterized in that The dispersant is a polysiloxane dispersant.
8. A method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to claim 7, It is characterized in that The defoamer is a silicone defoamer.
9. A low surface energy super hydrophobic drag reduction anti-corrosion coating prepared by the method for preparing a low surface energy super hydrophobic drag reduction anti-corrosion coating according to any one of claims 1 to 8, It is characterized in that The drag reduction rate of the low surface energy super hydrophobic drag reduction and anti-corrosion coating reaches 32.9%.
Citation Information
Patent Citations
Super hydrophobic paint and preparation and construction methods thereof
CN107267030A
Wear-resistant superhydrophobic coating and preparation method thereof
CN109825165A
Wear-resistant and stable flame-retardant super-hydrophobic / super-oleophobic coating as well as preparation and application thereof
CN114250005A
Synthetic resin curtain wall decorative material for energy-saving building and preparation method of synthetic resin curtain wall decorative material
CN116285591A
Powdered polymer composition for a superhydrophobic coating and method for producing a superhydrophobic coating
US20160200915A1
